The Role of Family and School in Preparing Students for the General Secondary Certificate in Al-Ahsa Governorate - Mohammad Salman Al - Khazalah (Sultan Qaboos University, 2013)
This study aimed at identifying the role of the family and the role of school in preparing students for the General Secondary Certificate (GSC) in Al-Ahsa Governorate. The study sample consisted of 2000 students who were randomly selected (boys=1059, girls=941). The study found that the role of the family in preparing students for the General Secondary Certificate was high, but the role of school in such preparation was medium. The results indicated that there was no statistically significant gender difference in the role of the school. Academic stream,on the other hand, produced a statistically significant effect on the role of school in students preparation to GSC. Scientific stream students were better prepared than literary stream students. There was an interaction effect between gender and academic stream. In the scientific stream, males were higher, but in the literary stream females were higher. Also, there was significant difference between males and females regarding the role of family.